2017
DOI: 10.1007/s10910-017-0804-2
|View full text |Cite
|
Sign up to set email alerts
|

Positive equilibria of a class of power-law kinetics

Abstract: This paper studies a class of power-law kinetics, PL-ILK, for whose subset, PL-TIK, analogues of the Deficiency Zero Theorem and the Deficiency One Theorem (DOT) for mass action systems are valid. The DOT also includes the necessary and sufficient condition of Boros for uniqueness in the non-weakly reversible case. To our knowledge, this is the first set of kinetics beyond mass action kinetics (MAK) for which the DOT has been shown to be valid. A further interesting property of PL-TIK is a certain "robustness"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…We recall some fundamental notions about chemical reaction networks (CRNs) and chemical kinetic systems (CKS) assembled in [5,17]. Some concepts introduced by Feinberg in [9,10] are also reviewed.…”
Section: Fundamentals Of Chemical Reaction Network and Kinetic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recall some fundamental notions about chemical reaction networks (CRNs) and chemical kinetic systems (CKS) assembled in [5,17]. Some concepts introduced by Feinberg in [9,10] are also reviewed.…”
Section: Fundamentals Of Chemical Reaction Network and Kinetic Systemsmentioning
confidence: 99%
“…Savageau [15] and Voit [18,19] highlighted the advantages of using power-law formalism for modelling biochemical systems. In this light, many CRN-based results on PLK systems are established ( [6,11,13,17] among others), some of which are extensions or modifications of existing results on MAK systems.…”
Section: Introductionmentioning
confidence: 99%
“…In [16], D. Talabis introduced for any PL-RDK system the map F T := T •proj R • I a where R = R ρ(R) , which we now call the "truncated kinetic map".…”
Section: The Kinetic Flux Subspace Of a Pl-rdk Systemmentioning
confidence: 99%
“…In further papers [11,14] they refined their approach to construct linearly conjugate systems which are not only weakly reversible but also have desirable deficiency properties: minimal deficiency and satisfying the Deficiency One Theorem conditions. Since Deficiency Theory for PL-RDK systems is little developed (s. [21] for a detailed discussion), we focus only on extending the first algorithm for constructing weakly reversible linear conjugate systems.…”
Section: Adaptation Of the Johnston Et Al Milp Algorithm To Pl-rdk Smentioning
confidence: 99%
“…. In [1], it is shown that PL-RDK systems are precisely the power law systems for [16] (which we call GMAK-14) are discussed in detail in [21]. We specify the kinetics of PL-RDK systems with their rate vector and T matrix.…”
Section: Introductionmentioning
confidence: 99%